The Benefits of Introducing a Pregnancy Support Tool for Low-Income Women During Routine Obstetrics Care - Anne Rivelli; Veronica Fitzpatrick; Maureen Shields; Kim Erwin; Leah Delfinado; Marie Cabiya; Karen Wennerberg (SAGE Publishing, 2023)
The objective of the CONTINUE (conversations in routine OB care) pilot study was to gather preliminary data on the benefits of integrating a well-designed pregnancy support tool ("CONTINUE Tool") in low-income prenatal care. A total of 184 tools were distributed by 21 OB providers during the study implementation period. Follow-up data were collected from 71 (38.5%) prenatal patients across three community-based midwestern OB clinics serving a diverse prenatal patient population. Early-gestation prenatal patients received the strategically designed CONTINUE Tool during routine prenatal care and later completed a semi-structured interview or electronic survey to report pre-determined individual benefit items experienced due to tool usage. Factor analysis used individual benefit items to identify factors representing common underlying benefits ("factor benefits"). Logistic regression analyses were performed to describe the relative odds of participants with low income (public insurance) experiencing individual and factor benefits of tool use compared to participants of higher income (private insurance). Chi square tests (or Fisher's exact tests) were performed to generate P values reflecting statistically significant differences by income group. More low-income prenatal participants reported experiencing individual benefits as compared to higher-income participants. Among factor benefits, low-income participants were statistically more likely to report experiencing a time-related logistics benefit (OR = 4.00; 95% CI 1.02-15.73; P  = .045). Low-income participants reported experiencing an overall logistics factor benefit (OR = 4.29; 95% CI 0.47-38.75), including a cost-related logistics benefit (OR = 3.08; CI 0.59-16.00), as well as an understanding benefit (OR = 1.90; 95% CI 0.72-5.04) and a self-efficacy benefit (OR = 1.30; 95% CI 0.44-3.87). While this study is limited by sample size due to being a pilot study, the findings suggest there may be tangible benefits to introducing the CONTINUE Tool among low-income prenatal patients. Given the staggering inequity in OB care and subsequent health outcomes, any preliminary findings on ways to help combat this are necessary and should lay the groundwork for subsequent randomized trials. Our preliminary findings show that supplementing routine OB care with the CONTINUE Tool can confer benefits to both providers and patients, but particularly for low-income prenatal patients who tend to have more structural barriers to adequate care in the first place.